2020
DOI: 10.1177/0194599820964737
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation vs Electrocautery Blinded Randomized Trial: Impact on Clinically Meaningful Outcomes

Abstract: Objective To analyze patients’ return to normal activity, pain scores, narcotic use, and adverse events after undergoing tonsillectomy or adenotonsillectomy with monopolar electrocautery or radiofrequency ablation. Study Design Randomized double-blinded clinical trial based on prospective parallel design. Setting Academic medical center and tertiary children’s hospital between March 2018 and July 2019. Methods Inclusion criteria included patients aged ≥3 years with surgical indication of recurrent tonsillitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…In one of the largest randomized controlled trials, Prussin et al did not observe any difference in postoperative pain between MEC and coblation. 6 Of note, pain scores in their coblation group 1 day postsurgery were significantly lower than in their MEC group, which was mostly similar to the pain scores of MEC and coblation groups within 1 day postsurgery in the present study. 6 Tan et al also did not note any difference in pain scores between their coblation and MEC groups; however, Magdy et al reported that coblation was associated with less pain than MEC.…”
Section: ããsupporting
confidence: 82%
See 2 more Smart Citations
“…In one of the largest randomized controlled trials, Prussin et al did not observe any difference in postoperative pain between MEC and coblation. 6 Of note, pain scores in their coblation group 1 day postsurgery were significantly lower than in their MEC group, which was mostly similar to the pain scores of MEC and coblation groups within 1 day postsurgery in the present study. 6 Tan et al also did not note any difference in pain scores between their coblation and MEC groups; however, Magdy et al reported that coblation was associated with less pain than MEC.…”
Section: ããsupporting
confidence: 82%
“…Earlier studies reported that coblation causes more post-tonsillectomy bleeding than other techniques; however, more recent studies on MEC versus coblation and CSD versus coblation report there are no differences in bleeding rates, which might be attributed to gains in surgical proficiency over time. 6,11,[20][21][22] In contrast, a 2013 review reported that CSD was associated with the least delayed post-tonsillectomy bleeding. 23 Differences in the reported rates of post-tonsillectomy bleeding might be due to nonhomogenous patient groups and nonstandardization of surgical techniques (e.g., using a combination of 2 techniques).…”
Section: ããmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiofrequency ablation is a minimally invasive technique to eliminate pathological changes by generating heat from high-frequency radio frequency waves, which leads to cell coagulation and necrosis [ 10 ]. Electrocautery is performed by direct electrocautery of the diseased tissue with a high-frequency electrotome [ 11 ]. In recent years, there is little information about VaIN treatment by the two methods.…”
Section: Introductionmentioning
confidence: 99%
“…One study (9) reported 2 types of postoperative bleeding, coblation (3%) and electrocautery (3.4%), and there was no significant difference between the 2 groups (P>0.05). It was reported in another study (17) that there were 6 cases of bleeding, 2 cases of vomiting, 3 cases of dehydration, and a total of 17 cases (15.2%) of complications after coblation, while there were 2 cases of bleeding, 3 cases of vomiting, 2 cases of dehydration, and a total of 20 cases (16.9%) of complications after electrocautery. There was no significant difference in the incidence rate of total complications between the 2 groups (P>0.05).…”
Section: Postoperative Complicationsmentioning
confidence: 89%